The conceptual framework for the therapeutic approach used in phase 3 trials of MDMA-assisted therapy for PTSD - O’Donnell, Kelley C.; Okano, Lauren; Alpert, Michael; Nicholas, Christopher R.; Thomas, Chantelle; Poulter, Bruce; Mithoefer, Ann; Mithoefer, Michael; Ot’alora G, Marcela (Frontiers in Psychology, 2024)
Results from multiple recent studies support further evaluation of 3,4methylenedioxymethamphetamine (MDMA) in conjunction with psychotherapy (i.e., MDMA-Assisted Therapy) in the treatment of post-traumatic stress disorder (PTSD). In two Phase 3 trials, MDMA-Assisted Therapy comprised a short-term, intensive psychotherapy that included three sessions directly facilitated by MDMA (referred to as "experimental sessions"), as well as a number of non-drug psychotherapy sessions. This treatment model aimed to harness the potential of MDMA to facilitate recall and processing of traumatic memories, and to increase learning in a social context, integrating "top-down" and "bottom-up" approaches to traumafocused care. To date, the conceptual framework for this treatment has not been described in the scientific literature. This omission has contributed to misunderstandings about both the theoretical underpinnings of this modality and the therapeutic approach that emerges from it. This paper delineates the psychotherapeutic concepts, theories, and historical antecedents underlying the inner-directed approach to MDMA-Assisted Therapy for PTSD. Broadly speaking, this therapeutic framework centered the concept of the participant's inner healing intelligence as the primary agent of change, with the therapeutic relationship being the core facilitative condition fostering the participant's self-directed movement toward recovery and growth.Corollaries to this holistic, self-directed, relational, and trauma-informed framework include a non-pathologizing approach to the participant's embodied experience (including the possibility of intense emotional and somatic expression, experiences of multiplicity, suicidal ideation, and multigenerational and transpersonal experiences), as well as the therapists' own psychodynamic, somatic, and transpersonal awareness, empathic attunement, relational skillfulness, and cultural humility. The use of MDMA in conjunction with this psychotherapy platform outperformed the use of placebo with psychotherapy in Phase 2 and 3 trials, as measured by symptom reduction in participants with PTSD. However, within-group comparisons also identified significant symptom reduction in participants who did not receive MDMA, lending empirical support to the psychotherapy model itself. In addition to comparative efficacy trials, future research should investigate which elements of the conceptual framework and therapeutic approach underlie the clinical benefit in individuals with PTSD.